IMPLEMENTASI FILE SERVER TERPUSAT MENGGUNAKAN NEXTCLOUD DI SMKN 2 KUTACANE - Maila Sundari; Nazaruddin Ahmad (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
This study discusses the implementation of a centralized file server system using Nextcloud at SMKN 2 Kutacane to improve the efficiency and security of internal data management. The system was developed on a local server running Ubuntu Server and the Nextcloud application, which provides internal cloud storage via intranet. The development process followed the ADDIE model, including needs analysis, system design, installation, implementation, and evaluation. Evaluation involved blackbox testing to assess system functionality, along with user observations and questionnaires to explore user perceptions. The results indicate that the system operated as expected, was easy to use, and significantly enhanced digital collaboration within the school. These findings suggest that local cloud technology can be effectively adopted by vocational education institutions to support cost-efficient and controlled digital transformation.